Impelementasi Taksonomi Bloom Revisi dalam Pengembangan Instrumen Berbasis Hots - Ferni Adelfia Mboro; Dina Moyah; Yopi Bois; Roimanson Panjaitan (Jurnal Pendidikan Agama dan Teologi, 2026)
Higher-order thinking skills (HOTS) are a requirement in 21st-century education, yet assessments in schools are still primarily based on lower-order thinking (LOTS) cognitive skills. This study aims to examine the concept of the Revised Bloom's Taxonomy, the characteristics of instruments based on Higher-Order Thinking Skills (HOTS), and their implementation in instrument development. This study used a qualitative approach with a heritage study method. Data were obtained from books, scientific journals, and educational policy documents related to HOTS-based assessment. Analysis was conducted through data reduction, categorization, and drawing conclusions based on their alignment with the Revised Bloom's Taxonomy framework. The results of this study indicate that cognitive levels C4-C6 in the Revised Bloom's Taxonomy serve as the primary reference in developing HOTS instruments, which can assist in developing HOTS-based instruments to measure students' higher-order thinking skills.